KEMATANGAN EMOSI DALAM MENGHADAPI QUARTER LIFE CRISIS PADA MAHASISWA DI JOMBANG - Firmansyah, Dedy; Mufidah, Wardatul; Wigati, Denok (Universitas Darul Ulum, 2024)
This research aims to determine the influence of emotional maturity in facing the quarter life crisis in students. The Hypothesis porposed in thius reseacrh is that there is an influence of emotional maturity in facing the quarter lufe crisis. The reseacrh method used in the reseacrh is a quantitative method. The subjects in this students aged 19-25 years old who were inemployement. This research use purposive as a sampling method. This research uses product moments which are used to analyze data obtainerd using SPSS programs. The result of the hypothesis test there is a significant negative correlation between emotional maturity and quarter life crisis.